2017
DOI: 10.1021/acsami.7b00900
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Two to Tango—Double-Layer Selective Contacts in Perovskite Solar Cells for Improved Device Performance and Reduced Hysteresis

Abstract: Solar cells made from inorganic-organic perovskites have gradually approached market requirements as their efficiency and stability have improved tremendously in recent years. Planar low-temperature processed perovskite solar cells are advantageous for possible large-scale production but are more prone to exhibiting photocurrent hysteresis, especially in the regular n-i-p structure. Here, a systematic characterization of different electron selective contacts with a variety of chemical and electrical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 59 publications
6
87
0
Order By: Relevance
“…According to the literature, hysteresis occurs especially in planar n–i–p perovskite devices, as the contact area between TiO x and perovskite is reduced compared to mesoporous devices . Hence, TiO x with its low electron extraction properties is not well‐suited as ETL for planar devices.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, hysteresis occurs especially in planar n–i–p perovskite devices, as the contact area between TiO x and perovskite is reduced compared to mesoporous devices . Hence, TiO x with its low electron extraction properties is not well‐suited as ETL for planar devices.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Recently, Kim et al investigated the effects of methylammonium chloride (MACl) on the performance of perovskite films and fabricated a device that achieved a certified PCE of 23.5%. [9] Among them, TiO 2 , [10] SnO 2 , [11] and [6]-phenyl-C 61 -butyric acid methyl ester (PCBM) [12] are the most commonly used ones.The lower efficiency of devices based on planar structures is closely related to insufficient charge extraction [13] and imperfect interfacial band alignment. Developing low-temperature-processed electron-transport layer (ETL) [8] for planar structure devices is of great importance.…”
mentioning
confidence: 99%
“…The lower efficiency of devices based on planar structures is closely related to insufficient charge extraction [13] and imperfect interfacial band alignment. [14] The insufficient charge extraction between perovskite and ETL can result in charge accumulation, which negatively affects device performance.…”
mentioning
confidence: 99%
“…Xing et al [24] showed that there are high density hole-deficient traps located at the TiO 2 surface, which leads to an electron transfer potential barrier between CH 3 NH 3 PbI 3 and TiO 2 . This potential barrier is absent between the perovskite layer and the PCBM layer, and then the PCBM layer has a faster charge extraction compared to TiO 2 [24,25]. In order to ensure the function of PCBM, the PCBM layer should be avoided from the damage when the perovskite precursor is deposited.…”
Section: Resultsmentioning
confidence: 99%